Uso de um Modelo de Interceptadores para Prover Adaptação Dinâmica no InteGrade - OLIVEIRA NETO, Jesus José de (2008)
Computer grids are sets of computational resources that provide diverse types of services, such as storage and processing, on behalf of applications spread across different administrative domains. Many companies and academic institutions have demonstrated interest in their use for the execution of applications that demand huge amounts of computation power and storage. However, computer grids are complex and diversified execution environments, which exhibit high variation of resource availability, node instability and variations on load distribution, among other problems. This work presents a model of dynamic interceptors and its use in InteGrade, an opportunistic grid middleware. The use of interceptors aims to provide dynamic adaptation in InteGrade through its communication middleware, thus contributing to make InteGrade able to deal with the highly variable execution environment of computer grids without requiring changes to its implementation. Therefore, this work aims to offer dynamic adaptation capabilities to InteGrade and not to grid applications. Nevertheless, these applications will be able to benefit from adaptation provided by InteGrade